Pemanfaatan Personal Branding Selebram Fian Muh dalam Membangun Brand Awareness Axegear Melalui Media Sosial Instagram - Fadila, Asti; Siregar, Ballian; Heryati, Euis; Nurul Bahriyah, Euis (FISIP UPNVJ, 2025)
This study aims to determine how the personal branding of Instagram celebrity Fian Muh is utilized as a brand ambassador in building brand awareness of Axegear. This study is based on the importance of the role of brand ambassadors through a digital communication approach, especially social media, that is able to create emotional connections with the audience. The study uses a post-positivist paradigm, a descriptive qualitative method with an explanatory single case study approach. Data were collected through social media content observation, in-depth interviews with internal company members and followers, and literature studies. The results of the study indicate that Fian Muh's personal branding characteristics, including personal uniqueness, authentic character, branding consistency, positive reputation, and communication flexibility, are strategically utilized to increase brand visibility, strengthen credibility, and encourage audience engagement. These personal branding characteristics have been proven effective in increasing the number of followers, engagement rates, and shaping Axegear's image as a strong adventure brand in the trail bike community. The conclusion of the study shows that well-managed personal branding can be a strategic asset in public relations practices, especially for local brands, in building sustainable brand awareness.